An unrecognized group of chambered cairns - Childe, V Gordon (Proceedings of the Society of Antiquaries of Scotland, 1944)
A previously unrecognised group of chambered cairns have recently been identified in a 'blank' belt from the Dornoch Firth to the Cromarty Firth. The list comprises a regular chain of fourteen long or chambered cairns beginning just west of Edderton and extending along the foothills of Easter Ross overlooking the Cromarty Firth almost to the mouth of the Conon, together with eight comparable monuments east of that firth on the Black Isle. Only three of the monuments have previously been described. The relationship of these monuments to the Clava and Pentland types is considered and each of them is described in detail.